The Role of Digital Learning in Addressing Learning Loss in EFL Learning and Teaching from Teachers’ Perspectives - Khawaji, Taha Mansor (Journal of Posthumanism, 2025)
This qualitative study explored English teachers’ perspectives on the efficacy of digital learning in mitigating learning loss in EFL context. Semi-structured interviews with ten Saudi EFL teachers were thematically analyzed to examine their experiences, challenges, and best practices regarding digital language instruction. The findings revealed that digital learning platforms enhance accessibility, flexibility, engagement, and self-directed learning. However, several challenges hinder the effective implementation of digital learning in EFL education, including parental intervention, socioeconomic disparities, insufficient teacher training and professional development, increased workload, and large class size. Teachers observed that digital tools effectively support pronunciation, listening, and reading skills but struggle to replicate the interactive dynamics needed to develop speaking and writing proficiency. Despite these challenges, strategies such as flipped learning, collaborative activities, and fostering self-learning skills have proven to be effective in mitigating learning loss. This study underscores the importance of targeted training and continuous professional development in enhancing teachers’ skills in integrating modern technology and employing appropriate teaching practices. It recommends enhancements to adopting effective pedagogical strategies to enhance digital learning efficacy, and digital platforms that support real-time interactions to reduce learning loss and increase proficiency in the English language in digital learning environments.